2018
DOI: 10.3390/ph11030072
|View full text |Cite
|
Sign up to set email alerts
|

An Antioxidant Potential, Quantum-Chemical and Molecular Docking Study of the Major Chemical Constituents Present in the Leaves of Curatella americana Linn

Abstract: Reactive oxygen species (ROS) are continuously generated in the normal biological systems, primarily by enzymes as xanthine oxidase (XO). The inappropriate scavenging or inhibition of ROS has been considered to be linked with aging, inflammatory disorders, and chronic diseases. Therefore, many plants and their products have been investigated as natural antioxidants for their potential use in preventive medicine. The leaves and bark extracts of Curatella americana Linn. were described in scientific research as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 76 publications
6
30
0
Order By: Relevance
“…https://doi.org/10.1371/journal.pone.0225514.t004 antioxidant activity of this species through the capture of ROS previously demonstrated by Lopes et al and Fujishima et al [21,43]. The mass spectrum of HECA revealed the presence of flavonoids, terpenoids, phenolic derivatives confirming studies performed by El-Azizi et al and Gurni & Kubitzki [44,45].…”
Section: Discussionsupporting
confidence: 82%
“…https://doi.org/10.1371/journal.pone.0225514.t004 antioxidant activity of this species through the capture of ROS previously demonstrated by Lopes et al and Fujishima et al [21,43]. The mass spectrum of HECA revealed the presence of flavonoids, terpenoids, phenolic derivatives confirming studies performed by El-Azizi et al and Gurni & Kubitzki [44,45].…”
Section: Discussionsupporting
confidence: 82%
“…These compounds can also be used in the food industry to maintain the physical-chemical quality of fruits, meat, and other foods [14][15][16]. Due to the side effects of synthetic antioxidants, those from natural sources are preferred; this context leads to a constant search for plant-derived compounds with this property [4,[10][11][12][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The present of a methoxy at C-4′ in the ring C of tricin promotes the XO inhibitory activity. XO is also a main biological source of ROS, which cause DNA oxidation, protein degradation, and lipid peroxidation [ 11 ]. Thus, the inhibitory activity on XO may have simultaneously antihyperuricemia and antioxidant properties with therapeutic interest.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structures of the XO enzyme (PDB ID and 3NRZ) from fresh, unpasteurized bovine milk were used for the docking calculations [ 31 ]. For validation of the credible docking method, the natural ligands (hypoxanthine) were docked back into the relevant protein as a control until the root mean square deviation (RMSD) of the best-docked ligand conformation was less than 2.0 Å [ 11 ]. The docking results showed that a total of nine conformational clusters were obtained from 100 docking runs at a RMSD tolerance of 2.0 Å, and the highest number (57 out of 100) cluster was found to have the lowest binding energy (−7.59 kcal/mol, red histogram in Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation